Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/15384101.2018.1456296
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles of RAD18 and Y-family DNA polymerases in tumorigenesis

Abstract: Mutagenesis is a hallmark and enabling characteristic of cancer cells. The E3 ubiquitin ligase RAD18 and its downstream effectors, the ‘Y-family’ Trans-Lesion Synthesis (TLS) DNA polymerases, confer DNA damage tolerance at the expense of DNA replication fidelity. Thus, RAD18 and TLS polymerases are attractive candidate mediators of mutagenesis and carcinogenesis. The skin cancer-propensity disorder xeroderma pigmentosum-variant (XPV) is caused by defects in the Y-family DNA polymerase Pol eta (Polη). However i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 108 publications
0
31
0
Order By: Relevance
“…There are 95 Rad18 variants distinguishing B6J from D2J https://www.sanger.ac.uk), including five, 3' UTR variants, 25 intronic nmd variants, and one 7 Kb structural variant (deletion) (see Supplementary Table 1 for high impact variants). Rad18 dysfunction can lead to mutagenesis, carcinogenesis, and tumorigenesis (Yang et al 2018). Expression QTLs from several brain tissues were linked to Rad18 expression which, in turn, were correlated with several traits related to BW, metabolism, emotional, and substance use disorder traits (Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…There are 95 Rad18 variants distinguishing B6J from D2J https://www.sanger.ac.uk), including five, 3' UTR variants, 25 intronic nmd variants, and one 7 Kb structural variant (deletion) (see Supplementary Table 1 for high impact variants). Rad18 dysfunction can lead to mutagenesis, carcinogenesis, and tumorigenesis (Yang et al 2018). Expression QTLs from several brain tissues were linked to Rad18 expression which, in turn, were correlated with several traits related to BW, metabolism, emotional, and substance use disorder traits (Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…This overexpression likely results in the increased monoubiquitination of PCNA, inappropriately activating TLS to drive cancer mutagenesis. Rad18 overexpression is commonly coupled with overexpression of its binding partner Melanoma Antigen-A4 (MAGE-A4) [ 91 ]. MAGE-A4 overexpression stabilizes Rad18 by protecting it from ubiquitin-mediated degradation, allowing for its continued over-activation in cancer cells [ 92 ].…”
Section: Dna Damage Bypass and Cancermentioning
confidence: 99%
“…The E3 ubiquitin-protein ligase RAD18 plays a vital role in DNA damage bypass and post-replication repair (PRR) through the promotion of proliferating cell nuclear antigen (PCNA) mono-ubiquitination at stalled replication forks (3). Recent studies have shown that high expression of RAD18 in cancerous tissues is associated with cancer metastasis and tumor progression in a variety of cancers (4)(5)(6). In melanoma, studies demonstrated that RAD18 participates in the regulation of cell proliferation, and its high expression is associated with poor five-year patient survival (7).…”
Section: Introductionmentioning
confidence: 99%